PENANGANAN ANAK PUTUS SEKOLAH DI JAWA TENGAH - Mursid Zuhri; Resti Dwiyantoro (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
In 2011 Human Development Index ranking (Human Development Index) Indonesia dropped in position 69 of 127 countries drop out rate in Central Java at primary level is quite high. A total of 527 850 children or 1.7% of the 31.05 million children drop out of school each year. The decline in the composite index of education, as the pressures of poverty causes poor families are forced to sacrifice the continuity of children's education. Spread the dropout rate for elementary education / MI RPJMD is already close to the target of 0.12% by 2013. But there are still quite high at 501 for cilacap District, 542 Brebes and Tegal 499. For MI SD is relatively small compared Cilacap, 34, 130 and Bradford counties Tegal 54 As for the education level of SMP / MTS Cilacap, 290 Brebes Tegal 612 and 643. While MTS Cilacap, 118 districts Brebes and Tegal 109 and 125 (source Disdik Prov). Based on field data, the number of school dropouts is much higher. Causes of school children is because children from poor kelauarga generally forced to work to help their parents, both in the domestic activities of the household and for public sector jobs that generate income: Child labor is treated as a substitute bp / mother, their time is taken engage in productive and domestic activities. The main zoning model of community involvement in the school (PKBM, SATAP) realistic enough to be developed, and the involvement of the Board of Education committee on the level needs to be increased role dikembangkn upt ill and confined to the Division of alternative management and financing of education in the treatment of ATS. Recommendations that can be delivered is through the handling model school children should learn from empirical conditions in these areas, through revitalization, facilitation (1) Community Learning Center Group (PKBM) in certain areas (2) SATAP for junior high school particularly isolated areas. Providing PKBM for children out of school and out of school is very helpful for those who can not afford the time and willingness. As happened in the village PKBM Malahayu unatuk pastoralist cattle, goats; PKBM in Nusawungu and PKBM in Pangkah, Kedungreja; Socialization Program Fair 9-year improved. While also optimizing the role of the Board of Education, the School Committee Level Forum Communications Unit and the School Committee Joint Education Unit Level SKPD not limited to education alone.